Melt‐Centrifuged (Bi, Sb)2Te3: Engineering Microstructure toward High Thermoelectric Efficiency. Issue 34 (8th July 2018) - Pan, Yu; Aydemir, Umut; Grovogui, Jann A.; Witting, Ian T.; Hanus, Riley; Xu, Yaobin; Wu, Jinsong; Wu, Chao‐Feng; Sun, Fu‐Hua; Zhuang, Hua‐Lu; Dong, Jin‐Feng; Li, Jing‐Feng; et al.
Abstract: Microstructure engineering is an effective strategy to reduce lattice thermal conductivity (κl ) and enhance the thermoelectric figure of merit ( zT ). Through a new process based on melt‐centrifugation to squeeze out excess eutectic liquid, microstructure modulation is realized to manipulate the formation of dislocations and clean grain boundaries, resulting in a porous network with a platelet structure. In this way, phonon transport is strongly disrupted by a combination of porosity, pore surfaces/junctions, grain boundaries, and lattice dislocations. These collectively result in a ≈60% reduction of κl compared to zone melted ingot, while the charge carriers remain relatively mobile across the liquid‐fused grains. This porous material displays a zT value of 1.2, which is higher than fully dense conventional zone melted ingots and hot pressed (Bi, Sb)2 Te3 alloys. A segmented leg of melt‐centrifuged Bi0.5 Sb1.5 Te3 and Bi0.3 Sb1.7 Te3 could produce a high device ZT exceeding 1.0 over the whole temperature range of 323–523 K and an efficiency up to 9%. The present work demonstrates a method for synthesizing high‐efficiency porous thermoelectric materials through an unconventional melt‐centrifugation technique. Abstract : The melt‐centrifugation technique is demonstrated to be able to decrease the thermal conductivity while preserving the good electrical properties. By introducing a unique porous structure with microscale dislocation, ≈60% reduction in lattice thermal conductivity compared to conventional zone melted ingots is achieved. Such a method paves a new way for top‐down introduction of large porosity and dense dislocations in bulk materials.